Conjugal Homes with Double Supply in Colombia. Contributions for the Construction of a Typology of Labor Arrangements with Gender Approach - Bermúdez-Rico, Rosa Emilia; Melo-Morales, Paola Julieth (Sociedad y Economía, 2019)
The purpose of this article consists in establishing a classification labor arrangements of conjugal homes with double supply in Colombia, considering the participation in the market understanding the differences between sexs in a conjugal relationship. This analysis contributes to a better understanding of the meaning between “work” and “gender” in these kind of homes in contemporary societies. With that purpose in mind, we establish the analytical category “conjugal home according to labor arrangement”, and all the information provided by the Nacional del Uso del Tiempo survey (ENUT 2012-2013) is processed. With this procedure, a typology of labor arrangements that we identify in Colombian homes is established. The analysis emphasizes the high participation levels that these type of homes have reached in urban contexs in the country and the high educational level of the couples that conform said homes.